2018
DOI: 10.1128/jvi.00901-18
|View full text |Cite
|
Sign up to set email alerts
|

CD32 + and PD-1 + Lymph Node CD4 T Cells Support Persistent HIV-1 Transcription in Treated Aviremic Individuals

Abstract: The existence of long-lived latently infected resting memory CD4 T cells represents a major obstacle to the eradication of HIV infection. Identifying cell markers defining latently infected cells containing replication-competent virus is important in order to determine the mechanisms of HIV persistence and to develop novel therapeutic strategies to cure HIV infection. We provide evidence that PD-1 and CD32 may have a complementary role in better defining CD4 T cell populations infected with HIV-1. Furthermore,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Subsequently, we compared the characteristics of CD4 + α4β7 + versus α4β7 - cells in terms of activation status (HLA-DR) and exhaustion status (PD-1) as well as CD39 and CCR5 expression ( Fig 3A–3D ). Cells that express high levels of the programmed cell death protein-1 (PD-1) have been shown to be a critical source of replication-competent HI virus in patients on ART [23,24]. Thus, the molecule has been proposed to be one of the markers describing the latent reservoir and its relation to α4β7 expression on different T-cell subsets is not known.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we compared the characteristics of CD4 + α4β7 + versus α4β7 - cells in terms of activation status (HLA-DR) and exhaustion status (PD-1) as well as CD39 and CCR5 expression ( Fig 3A–3D ). Cells that express high levels of the programmed cell death protein-1 (PD-1) have been shown to be a critical source of replication-competent HI virus in patients on ART [23,24]. Thus, the molecule has been proposed to be one of the markers describing the latent reservoir and its relation to α4β7 expression on different T-cell subsets is not known.…”
Section: Resultsmentioning
confidence: 99%
“…Most activated CD4 + T-cells die from HIV cytopathogenicity or immune-mediated cell death. Compared with healthy controls, the expression levels of PD-1, CTLA-4, TIM-3, LAG-3, and TIGIT on effector CD4 + T-cells are elevated to varying degrees, accompanied by CD4 + T-cell function impairment and disease progression [47,[50][51][52][98][99][100]. For example, upregulation of PD-1 and CTLA-4 expression is associated with higher plasma viral loads and lower CD4 + T-cell counts.…”
Section: Hiv-specific T-cell Exhaustion Accompanies Immune Checkpointmentioning
confidence: 99%
“…Remarkably, we demonstrated a progressive increase in HIV DNA enrichment in CD32 + CD4 + cells with further purification of these cells, and in the purified population we measured a very prominent enrichment for HIV DNA (average, 292-fold) (106), confirming the results of Descours et al (99). Interestingly, several groups found that the majority of peripheral blood CD32 + CD4 + T cells express the activation marker HLA-DR (100102, 106, 108, 109). Although it has been shown previously that HIV can establish latent infection in activated CD4 + T cells (110, 111) and that the peripheral blood HIV DNA load is higher in activated compared to resting cells in ART-treated individuals (112), the existence of latently infected CD4+ cells that are activated, and therefore relatively short-lived, suggests continuous replenishment of this component of the reservoir by cellular proliferation (113).…”
Section: Cd32amentioning
confidence: 99%
“…Two groups studied co-expression of CD32a and other HIV reservoir markers in tissues. Noto et al analyzed HIV transcription in LN memory CD4 + T-cell populations sorted for CD32a and PD-1 expression (108). The CD32 + and PD-1 + CD4 + T-cell populations overlapped to a large extent and CD32 + PD-1 + cells were significantly enriched for HIV RNA compared to CD32 − PD-1 − , CD32 + PD-1 − , and CD32 − PD-1 + cells.…”
Section: Cd32amentioning
confidence: 99%